Comparison of oral and intravenous cyclophosphamide in children with steroid-resistant nephrotic syndrome - Eka Laksmi Hidayati; Sudung O. Pardede; Partini P. Trihono (Paediatrica Indonesiana, 2011)
Background There are variations in remission rates following treatment of steroid-resistant nephrotic syndrome (SRNS) with cyclophosphamide.Objective To compare the efficacy of oral versus intravenous cyclophosphamide (CPA) in the management of pediatric SRNS.Methods This was a prospective study of 41 children with SRNS treated with CPA. One group received oral CPA at a dose of 2 mg/kg body weight/day for 8-12 weeks, while the other group received intravenous CPA at a dose of 500mg/m2 body surface area (BSA) monthly for 6 months. All patients were concomitantly treated with prednisone on alternate days. The primary outcome was the number of patients attaining remission.Results The study was comprised of 20 children receiving oral CPA and 21 children receiving intravenous CPA. There were 29 boys and 12 girls. The mean age of children at the onset of nephrotic syndrome (NS) was 47 ± 40 months old (range 12 months – 13 years), and the mean duration of NS before initiation of CPA therapy was 15 ± 28 months (range 1 – 129 months). Remission was achieved in 29 (70.7%) patients, with no difference between oral and intravenous route of CPA administration. The mean time to achieve remission was 22.7 weeks (about 5 months). The oral route group required less time in achieving remission than the intravenous route group. No association was found between remission and other factors, such as onset of steroid resistance, route of CPA, hypertension and hematuria. Side-effects included infection, anemia, nausea/vomiting, and alopecia. None of the patients required discontinuation of the medication.Conclusion Oral CPA was as effective as intravenous CPA for children with steroid-resistant nephrotic syndrome. [Paediatr Indones. 2011;51:266-71].